2017
DOI: 10.11138/mltj/2017.7.1.136
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the menstrual cycle on lower-limb biomechanics, neuromuscular control, and anterior cruciate ligament injury risk: a systematic review

Abstract: SummaryObjective: Anterior cruciate ligament (ACL) injury has a devastating impact on physical and psychological disability. Rates of ACL rupture are significantly greater in females than males during the same sports. Hormonal mechanisms have been proposed but are complex and poorly understood. This systematic review evaluates the effects of menstrual cycle on: 1) lower-limb biomechanics, 2) neuromuscular control, and 3) ACL injury risk. Methods: The MEDLINE, CINAHL, SPORTSDiscus, Web of Science, and Google Sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(26 citation statements)
references
References 50 publications
0
24
0
2
Order By: Relevance
“…Information regarding menarche informed the appropriate time for biomechanical testing [13] as fluctuating estradiol levels in girls during and post-puberty may influence lower limb biomechanics [25, 26]. Participants who indicated that they had experienced menarche, but were not using a monophasic OCP, were tested within the first 7 days of their menstrual cycle (i.e., early follicular phase).…”
Section: Methodsmentioning
confidence: 99%
“…Information regarding menarche informed the appropriate time for biomechanical testing [13] as fluctuating estradiol levels in girls during and post-puberty may influence lower limb biomechanics [25, 26]. Participants who indicated that they had experienced menarche, but were not using a monophasic OCP, were tested within the first 7 days of their menstrual cycle (i.e., early follicular phase).…”
Section: Methodsmentioning
confidence: 99%
“…These aspects affect the trunk and hip flexion angles as well as hip adduction and internal rotation during sports movements, making women players prone to lower limb injuries [ 36 , 37 ]. So, the trunk, hip and knee joints need to be considered in women’s basketball players due to the high rate of anterior cruciate ligament injuries and the effect of external variables such as fatigue and the menstrual cycle on this injury process [ 38 , 39 ]. Therefore, the injury prevention protocols, training tasks and recovery programs should focus on the lower limbs in comparison with the upper limbs.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that hormonal levels and the associated modification in the collagen content are to be considered factors related to the increased risk of incidence of knee ligament injuries in the female population. [65][66][67][68] These ovarian hormones alter collagen metabolism by generating enzymes that cleave and denature tropocollagen molecules. In addition, the effect of advanced glycation end products (AGEs), a phenomenon observed in the elderly and diabetic populations as responsible for the increased risk of ligament injuries, 69,70 could be a potential target using the proposed model.…”
Section: Discussionmentioning
confidence: 99%